2018
DOI: 10.1148/radiol.2017171850
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Signal Intensity of the Dentate Nucleus and Globus Pallidus in Pediatric Patients: Impact of Brain Irradiation and Presence of Primary Brain Tumors Independent of Linear Gadolinium-based Contrast Agent Administration

Abstract: Purpose To determine whether whole-brain irradiation, chemotherapy, and primary brain pathologic conditions affect magnetic resonance (MR) imaging signal changes in pediatric patients independent of the administration of gadolinium-based contrast agents (GBCAs). Materials and Methods This institutional review board-approved, HIPAA-compliant study included 144 pediatric patients who underwent intravenous GBCA-enhanced MR imaging examinations (55 patients with primary brain tumors and whole-brain irradiation, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 33 publications
(23 reference statements)
5
29
0
Order By: Relevance
“…Although the results of our study demonstrated concordance with the results of Tamrazi et al (20) and Kinner et al (21) with regard to changes in signal intensity on T1-weighted images secondary to treatment, there does not appear to be a relationship between dose and signal intensity changes when treatment effects are accounted for, as was seen with a linear GBCA. This suggests that macrocyclic GBCAs have potentially different retention mechanisms in brain tissue than do linear GBCAs.…”
Section: Figuresupporting
confidence: 90%
See 2 more Smart Citations
“…Although the results of our study demonstrated concordance with the results of Tamrazi et al (20) and Kinner et al (21) with regard to changes in signal intensity on T1-weighted images secondary to treatment, there does not appear to be a relationship between dose and signal intensity changes when treatment effects are accounted for, as was seen with a linear GBCA. This suggests that macrocyclic GBCAs have potentially different retention mechanisms in brain tissue than do linear GBCAs.…”
Section: Figuresupporting
confidence: 90%
“…In our study, we found that the signal intensity in the DN on T1-weighted images was higher in children who had undergone brain irradiation than in those who had not received radiology.rsna.org n Radiology: Volume 289: Number 1-October 2018 ous study by Tamrazi et al (20), in which similar changes in pediatric patients with brain tumors with exposure to a linear GBCA were investigated, again suggesting that changes in T1-weighted signal intensity from radiation therapy exposure are independent of the type of GBCA-that is, a linear agent or, as in our current study, a macrocyclic agent. The results of our study also showed that the signal intensity on T1weighted images of the DN did not appear to have a dosedependent relationship with the gadobutrol administered.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Skin lesions associated with GBCA administration have been reported both in animal models and in human subjects is no explicit evidence of gadolinium directly transgressing the intact BBB. The mechanisms of transit across the blood-CSF barrier, retention in neural tissues, potential role of concomitant radiation or chemotherapy (94,95), and clearance via the glymphatic tissues are currently poorly understood.…”
Section: Retention Of Gadolinium In Non-cns Tissuesmentioning
confidence: 99%
“…In studies that report a SI increase, it is mandatory to consider the confounders of conditions that increase the concentration of manganese in the deep gray matter (parenteral feeding, exposure to manganese, portosystemic shunt) or certain disorders associated with an increase of the SI of the basal ganglia (neurofibromatosis type I, metabolic disorders, hypoxic-ischemic encephalopathy, etc.). The influence of radiation as a confounder is still a topic under investigation [52].…”
Section: -Assess Exclusively Si Differences/changes Measured With Commentioning
confidence: 99%